An 'ordinary novel': genre trouble in Radclyffe Hall's The Well of Loneliness. Issue 1 (2nd January 2018) - Roche, Hannah
ABSTRACT: Radclyffe Hall's The Well of Loneliness has long been read as stylistically inferior to novels by Hall's 'experimental' peers. Led by Virginia and Leonard Woolf, the dominant opinion has, to quote Terry Castle, sentenced Hall to a reputation of 'bad, bad, bad' writing. This article takes issue with Hall's exclusion from modernism, raising questions about the relationship between political radicalism and stylistic familiarity. Was Hall cleverly turning to a Victorian mode in order to critique the politics of modernism, challenging the value of aesthetic experiment and obscurity? I argue not only that The Well was stylistically as impressive as the most celebrated of 'difficult' 1920s novels, but also that, by boldly appropriating an accepted (and heteronormative) genre, Hall makes a statement about the rightful position of lesbian writing that dares to strike its readers in ways more direct and profound than the audaciously avant-garde.